Integration of Religious Values to Reduce the Decline of Adolescent Ethics in High School - Rozi, Fathor; Bulqis, Vicky Amalia; Fachri, Moh. (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Ethical decline among adolescents is one of the main challenges in education today. This study aims to examine how the integration of religious values into moral education can mitigate the ethical decline among adolescents at High School, a boarding school that combines religious and general education. This research used a case study approach with qualitative methodology, involving participant observation, in-depth interviews with teachers and students, and documentation. This research was conducted at Nurul Jadid High School. The results indicate that the integration of religious values into the curriculum and extracurricular activities plays a significant role in improving students' morals and ethics, particularly in the areas of discipline, respect, and responsibility. Furthermore, the role of teachers as moral role models and a positive school environment also influence the successful internalization of religious values in students. However, challenges in its implementation include the gap between the teaching of religious theory and the implementation of these values in daily life. This study recommends a more contextual and integrative approach to address this challenge and strengthen religion-based moral education.